KAJIAN STANDAR PELAYANAN MINIMAL BIDANG PERUMAHAN PADA KEGIATAN DI KABUPATEN TANGERANG (Studi Kasus: Kecamatan Kronjo dan Kecamatan Mauk Kabupaten Tangerang) - Sutomo, sutomo; Sarjono Puro; Kiki Maria; Asep Jauhari (Journal of Innovation Research and Knowledge, 2024)
Public services are a basic right for citizens that must be fulfilled by the state and government administrators. One of the public services in the housing sector is the Minimum Service Standards (SPM) for uninhabitable houses (RTLH) that are rehabilitated or relocated. SPM is also carried out for the construction of RTLH due to disasters. In order to support the development of livable housing (RLH), it is necessary to calculate the SPM achievements and evaluate the SPM for RLH activities in realizing social justice for the community. The aim of the research is to determine the achievements of the SPM for RLH Rehabilitation activities and evaluate the SPM for RLH activities. The method used in this research is a descriptive quantitative method by analyzing the data collection objectively using a scoring instrument and producing an evaluation criterion on a scale: (Good, Fair or Poor). Research locations in Pagenjahan Village, Kronjo District and Ketapang Village, Mauk District. The research results show: 1. Achievements of SPM for RLH Provision and Rehabilitation Activities in Tangerang Regency, a. post-disaster results achieved 100% category (Good), b. Relocation results achieved 100% category (Good); 2. Evaluation of SPM Provision and RLH Activities in Tangerang Regency, a. post-disaster results achieved 37.02% category (Poor), b. Relocation results achieved 56.99% category (Fair). The results of the SPM achievements in the RLH Provision and Rehabilitation activities by calculating the achievements obtained a percentage of 100% in the Post-Disaster and Relocation activities, in the Good category. The results of the SPM evaluation of RLH Provision and Rehabilitation Activities using scoring calculations showed different results, and tended to be less good, this happened due to a lack of monitoring of the documents created.